HUBUNGAN KELINCAHAN DENGAN KETERAMPILAN MENGGIRING BOLA PADA SISWA KELAS V.E SDN 006 PANGKALANKERINCI KAB. PELALAWAN - Dodi Julianto; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of students in class V,E of SDN 006 Pangkalan Kerinci Pelalawan District. Researcher found many student have deficiency of dribbling, visible when the student dribble imperfect, as the ball away from the feet, so that the ball easily captured opponent. It is influenced by physical conditions that agility. The purpose of this research is to see the correlation between agility with ball dribbling skills of Student class V.E of SDN 006 Pangkalan Kerinci Pelalawan District. Population in this research is all Student in class V of SDN 006 Pangkalan Kerinci Pelalawan District amount 22 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 22 people. Research instrument used suttle run test to agility and dribbling ball test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : that is result obtained from Student in class V.E of SDN 006 Pangkalan Kerinci Pelalawan District. Shows that there is correlation of the agility (X) with dribbling (Y) , which shows correlation rhitung = 0,462>rtabel = 0,433Key word : Agility, Dribbling.